Aplikasi Peralatan Tekuk Plat untuk Industri Berbasis Logam - UMARDANI, YUSUF; DARMANTO, SENO (Jurnal Pengabdian Vokasi, 2023)
The potential, opportunities and advantages of the metal industry in Mliwis Cepogo have not been able to drive the people's economy optimally. This condition will be even more complicated because the metal industry, especially in production units, is constrained by equipment for workmanship. The realization of service activities at Zazen Art Galeria partners is principally carried out by strengthening the copper engraving industry, especially production units with the application of plate bending machines. The application of plate bending machines can improve product quality and quantity and increase productivity in production units. The plate bending machine's performance can be improved by applying hydraulics as a plate driver/presser